2009
DOI: 10.1002/hep.22758
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial effects of sorafenib on splanchnic, intrahepatic, and portocollateral circulations in portal hypertensive and cirrhotic rats #

Abstract: Portal hypertension, the most important complication in patients with cirrhosis of the liver, is a serious and life-threatening disease for which there are few therapeutic options. Because angiogenesis is a pathological hallmark of portal hypertension, the goal of this study was to determine the effects of sorafenib-a potent inhibitor of proangiogenic vascular endothelial growth factor receptor 2 (VEGFR-2), platelet-derived growth factor receptor ␤ (PDGFR-␤), and Raf kinases-on splanchnic, intrahepatic, system… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

22
249
2
7

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 282 publications
(281 citation statements)
references
References 37 publications
22
249
2
7
Order By: Relevance
“…However, the findings extend nicely the principle observation from animal experiments 4 to the clinical setting, with about one-third of treated individuals showing an improvement in portal hypertension with sorafenib, an effect of about the same magnitude as can be expected from the treatment of portal hypertensive patients with nonselective b-blockers like propranolol or nadolol. 5 We agree with Procopet et al that for studying the antihypertensive effects of sorafenib, patients with HCC are not an ideal patient population, but for lack of other options to test the drug so far, both of our groups did resort to this group of patients to perform a proofof-principle study on the haemodynamic effects of sorafenib in humans.…”
Section: Acknowledgementsupporting
confidence: 82%
“…However, the findings extend nicely the principle observation from animal experiments 4 to the clinical setting, with about one-third of treated individuals showing an improvement in portal hypertension with sorafenib, an effect of about the same magnitude as can be expected from the treatment of portal hypertensive patients with nonselective b-blockers like propranolol or nadolol. 5 We agree with Procopet et al that for studying the antihypertensive effects of sorafenib, patients with HCC are not an ideal patient population, but for lack of other options to test the drug so far, both of our groups did resort to this group of patients to perform a proofof-principle study on the haemodynamic effects of sorafenib in humans.…”
Section: Acknowledgementsupporting
confidence: 82%
“…Sorafenib may have various effects on different cell types. Mejias et al first reported sorafenib ameliorated portal hypertension, intrahepatic fibrosis, inflammation, and angiogenesis in a cirrhotic rat model (19). Subsequent studies demonstrated sorafenib might reduce HSC proliferation, and inhibit the synthesis of fibrogenesis-related proteins and extracellular matrix (7,20,21).…”
Section: Discussionmentioning
confidence: 99%
“…16,17,36 However, very little is known regarding the mechanism underlying these effects. Our results largely extend these studies by identifying the mechanism for modulation of TGF-b signaling by sorafenib and highlighting the biological function of sorafenib in TGF-b-induced EMT and apoptosis in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…14,15 In addition to its established clinical benefits for patients with a broad range of tumor types, recent studies in rats have demonstrated that sorafenib has potential utility in the treatment of portal hypertension and cirrhosis. 16,17 However, a detailed understanding of the underlying molecular mechanism remains elusive. In the current study we identified a new function for sorafenib as an effective inhibitor of TGF-b signaling.…”
mentioning
confidence: 99%